Cellular and molecular toxicology - Williams, Dominic (Henry Stewart Talks, 2009)
Classification of adverse drug reactions, How this relates to the chemical structure of the offending drug, Understanding how variation in drug metabolism can contribute to clinical toxicity is important in designing pre-clinical models and screens, Case studies of drugs which can form reactive metabolites and can irreversibly modify cellular protein, Examples of structural modifications to chemicals containing toxicophores, Novel and traditional serum and cellular biomarkers of adaptation, apoptosis and necrosis
Archived at 2016/06/15